Alpha-Lipoic Acid Ameliorates Sperm DNA Damage and Chromatin Integrity in Men with High DNA Damage: A Triple Blind Randomized Clinical Trial - Masoud Habibi; Behzad Abbasi; Zohreh Fakhari Zavareh; Vahid Esmaeili; Abdolhossein Shaverdi; Mohammad Ali Sadighi Gilani; Marziyeh Tavalaee; Mohammad Hossein Nasr Esfahani (Cell Journal, 2022)
Objective: Evidence suggests the contributory role of oxidative stress (OS) to sperm DNA damage and eventually, male infertility. Antioxidant supplementation has exhibited favorable results regarding seminal OS, sperm DNA damage, and chromatin integrity. We aimed to evaluate the effect of alpha-lipoic acid (ALA) supplementation on semen analysis, sperm DNA damage, chromatin integrity, and seminal/intracellular OS in infertile men with high sperm DNA damage.Materials and Methods: In this randomized triple-blind placebo-controlled clinical trial study, we opted for a triple-blind controlled clinical trial design. Considering the study’s inclusion criteria for the level of sperm DNA fragmentation (higher than the threshold of 30 and 15%), 70% of participants were selected for this clinical research study. Subjects were divided into case and control groups receiving oral ALA (600 mg/day) and placebo for eighty days, respectively. Sperm parameters and functional tests were examined and compared before and after treatment. The final sample size was 34 and 29 for ALA and placebo receivers, respectively.Results: No significant differences were observed about anthropometrics and baseline measures of semen analysis, DNA damage, OS, and chromatin integrity between the two groups. Conventional semen parameters were enhanced insignificantly in both groups (P>0.05). DNA damage decreased significantly in the ALA group, as per sperm chromatin structure assay (SCSA, P<0.001). Moreover, chromomycin A3 (CMA3) staining results indicated a decrease in nuclear protamine deficiency post-ALA therapy (P=0.004). Lipid peroxidation decreased significantly after treatment with ALA(P=0.003). Further, seminal antioxidant capacity/activity did not differ significantly in either of the groups (registration number: IRCT20190406043177N1).Conclusion: An 80-day course of oral ALA supplementation (600 mg/day) alleviates sperm OS, DNA damage, and chromatin integrity in men with high sperm DNA damage.